FiberNet—A new embolic protection device for carotid artery stenting. Issue 6 (9th November 2013) - Bauer, C.; Franke, J.; Bertog, S.C.; Woerner, V.; Ghasemzadeh‐Asl, S.; Sievert, H.
<x xml:space="preserve">Abstract</x> Background Though distal filter protection during carotid stenting reduces the risk of cerebrovascular events, periprocedural stroke remains a risk despite their broad usage. This observation may be related to the pore size of common filters. The FiberNet distal filter system is unique by its very small pore size (40 µm) as well as its low profile and flexibility. Little data is available regarding the clinical performance and safety of this device. Purpose The aim was the evaluation of the safety of the FiberNet embolic protection system during carotid artery stenting. Methods All consecutive patients treated with carotid stenting at our institution using the FiberNet device were systematically followed. Primary endpoint was the rate of all death and stroke within 30 days of the procedure. Results Carotid artery stenting using the FiberNet embolic protection system was performed in 54 patients. The procedure was technical successful in all patients. Three patients (5.5%) had a TIA. Amauosis fugax occurred in two patients (3.7%). One patient (1.9%) had a minor stroke with hemiparesis of the left arm and face which resolved completely within 48 hr after the procedure. No patient died or suffered a major stroke. Conclusion The safety and feasibility of the FiberNet distal protection system appears to be at least equivalent to that reported in studies using conventional distal filter protection. © 2013 Wiley Periodicals, Inc.